Pandangan yang Berbeda, Kepentingan yang Sama: Kemitraan Keamanan Jepang-India - Wicaksono, Satrio Agung (Jurusan Ilmu Politik Universitas Bangka Belitung, 2025)
Since the early Cold War era, Japan has cooperated exclusively with the United States in security matters. However, since the end of the Cold War, Japan began to diversify its bilateral security cooperation with other countries in the region, including those who do not necessarily share its immediate strategic interests, such as India. This article examines decision to choose India as its bilateral security partner, which started since 2008. This study relies on desk research, analyzing primary and secondary data collected from 2008-2025. The research applied qualitative deductive method and uses triangulation as an analytical tool. The analysis is grounded in neoclassical realism, which highlights the interaction between systemic pressures and domestic-level variables. Systemic factors examined included increasing maritime insecurity (terrorism and piracy) and the rise of Chinese maritime capabilities. In addition, the domestic perception and role of the foreign policy executive, particularly Prime Minister Abe, is taken into consideration. Findings from this research show that systemic pressures, especially from rising China,have pushed Japan to seek cooperation with like-minded regional actors. Furthermore, Abe’s “Confluence of the two seas” speech framed India as the linchpin in Japan’s Indo-Pacific strategy, citing its shared democratic values and status as a maritime states. These factors, combined with favorable elite perceptions of India, helped form Japan’s decision to choosing India as its security partner.